PENGARUH MODEL PEMBELAJARAN BERBASIS MASALAH TERHADAP HASIL BELAJAR IPAS PESERTA DIDIK KELAS V SDN 2 KEKERI - Sumandari; Syarifuddin; Ilham Handika (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the effect of problem-based learning models on the science learning outcomes of fifth grade students at SDN 2 Kekeri. This study used a quantitative approach with a quasi-experimental research design using a nonequivalent control group design. The population in this study was all fifth-grade students at SDN 2 Kekeri, with a sample size of 50 students consisting of an experimental class and a control class. The data collection technique used was a test in the form of a pretest and posttest. The data obtained was then analyzed using normality tests, homogeneity tests, and hypothesis tests with the help of the SPSS version 25 program. The results showed that the data was normally distributed and homogeneous. The results of the hypothesis test using the independent sample t-test obtained a t-value of 13.562, while the t-table value was 2.011 at a significance level of 0.05 with a significance value (2-tailed) of 0.000 < 0.05, so H0 was rejected and Ha was accepted. Thus, it can be concluded that there is an effect of the problem-based learning model on the IPAS learning outcomes of fifth-grade students at SDN 2 Kekeri. The problem-based learning model can improve student learning outcomes because it encourages students to be active in the learning process, think critically, and be able to solve problems related to the learning material.